Dinamica plantar en pruebas de balance, potencia, velocidad, y servicio en tenistas - Alfonso-Mora, M. L.; Castellanos Garrido, A. L.; Nieto Rodríguez, J. F.; Sánchez Baquero, H. A.; Táutiva Cárdenas, L. D. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2019)
The objective of this report is to describe the plantar dynamics during the tennis serve and during specific tests of power, speed, and balance in tennis players and to establish their relationships. A descriptive method was established in which 16 athletes were evaluated by tests of performing power, speed, balance, and top spin serving. Descriptive measures were made for the results of these tests and those of the plantar dynamics and were correlated with each other. The results suggest that the center of anteroposterior pressure of the foot (COP-AP) during the balance tests had an average of -32 mm; in turn, the average power during the jump in the serve was 165 ±35 N. A relationship (r = 0.45) was found between the time in the air and the centimeters jumped, along with a relationship between the time of the speed test and the time of the running cycle (r = 0.54).